Does the negative effect of caregiving on work persist over time? - Dörte Heger; Thorben Korfhage (RWI - Leibniz-Institut für Wirtschaftsforschung, 2017)
Informal caregivers provide valuable services to elderly persons with long-term care needs. However, the time commitment of caregiving often competes against time spent in the labour force. In addition to the momentary trade-off, long-term consequences are possible since especially older workers might find it difficult to re-enter the labour market after a caregiving spell. While several studies document a negative relationship between caregiving and work, little is known about whether this effect is persistent over time. Analysing a large panel data set of 15 European countries and Israel, we show that care provision to an elderly parent has lasting negative effects on employment for both men and women but only women reduce their working hours. – – Informell pflegende Angehörige leisten wertvolle Dienstleistungen für ältere Menschen mit Langzeitpflegebedarfen. Allerdings konkurriert diese zeitliche Verpflichtung der Betreuung oft mit der Zeit, die in bezahlter Arbeit verbracht werden kann. Zusätzlich zu kurzfristigen Effekten der Pflegetätigkeit auf das Arbeitsangebot der Pflegenden sind außerdem mittel- bis langfristige Konsequenzen denkbar, da es vor allem für ältere Arbeitnehmer schwierig sein könnten nach einem Austritt aus dem Arbeitsmarkt in den alten Job zurückzukehren oder eine neue Arbeit aufzunehmen. Dieser mittel- bis langfristige Effekt ist in der Literatur bisher wenig dokumentiert. Wir nutzen einen großen Panel-Datensatz mit 15 europäischen Ländern und Israel und zeigen, dass die Aufnahme einer Pflegetätigkeit anhaltend negative Auswirkungen auf die Beschäftigung hat. Dies gilt sowohl für Männer als auch für Frauen. Allerdings reduzieren nur Frauen auch ihre Arbeitszeit.
Keywords: J14; J22; 330; informal care; labour market outcomes; short and medium term effects